Analisis Fungsi Produksi Ternak Sapi Potong di Kabupaten Kuningan Jawa Barat - Rai Nasdian; Nunung Noor Hidayat; Sri Mastuti (Fakultas Peternakan Universitas Jenderal Soedirman, 2020)
Background. The purpose of this research was to determine the age factor of livestock production, forage feed, concentrate feed, enclosure density, medicines, bulk working hours, vitamins and minerals and PBBH Pasundan cattle and manalyze the effect of factors of production on PBBH Pasundan cattle in Kuningan Regency. Materials and methods. The object of research is 66 Pasundan bulls spread in 3 districts, namely; Cibingbin District (21 individuals), Maleber District (14 individuals) and Cimahi District (31). Retrieval of data using survey methods with questionnaire aids. Determination of the research area using purposive sampling method, while the determination of research objects using accidental sampling. The research variables observed were;(1) livestock age, (2) forage feed, (3) concentrate feed, (4) enclosure density, (5) medicines, (6) hours of work, (7) vitamins and minerals, (8) ADG. Results. Research result shows that the production factor influences 55.99% of the PBB Pasundan Cow. Together, the factors of production have a high significant effect on PBBH (F Hit <0.01). Partially the forage production factor, enclosure density, hours of work, vitamins and minerals have no significant effect on the ADG of Pasundan cattle. Conclusion. The conclusions of the study areaverage age of livestock 2.41 years, giving forage 15.95 kg /day/ST, giving concentrate 0.193 kg /day/ST, cage density 4,26 m2 / ST, the cost of medicines, vitamins and minerals Rp 4610.3/day/ST and Rp 846.8/day/ST., pouring out of working hours 1.64 hours/day/ST, and average of ADG is 0.32 kg/day/ST. ADG of Pasundan cattle are affected by age of livestock, concentrated feed and medicines.